Multilayered structure of tension wood cell walls in Salicaceae sensu lato and its taxonomic significance. (16th August 2016) - Ghislain, Barbara; Nicolini, Eric‐André; Romain, Raïssa; Ruelle, Julien; Yoshinaga, Arata; Alford, Mac H.; Clair, Bruno
Abstract : Salicaceae have been enlarged to include a majority of the species formerly placed in the polyphyletic tropical Flacourtiaceae. Several studies have reported a peculiar and infrequently formed multilayered structure of tension wood in four of the tropical genera. Tension wood is a tissue produced by trees to restore their vertical orientation and most studies have focused on trees developing tension wood by means of cellulose‐rich, gelatinous fibres, as in Populus and Salix (Salicaceae s.s .). This study aims to determine if the multilayered structure of tension wood is an anatomical characteristic common in other Salicaceae and, if so, how its distribution correlates to phylogenetic relationships. Therefore, we studied the tension wood of 14 genera of Salicaceae and two genera of Achariaceae, one genus of Goupiaceae and one genus of Lacistemataceae, families closely related to Salicaceae or formerly placed in Flacourtiaceae. Opposite wood and tension wood were compared with light microscopy and three‐dimensional laser scanning confocal microscopy. The results indicate that a multilayered structure of tension wood is common in the family except in Salix, Populus and one of their closest relatives, Idesia polycarpa . We suggest that tension wood may be a useful anatomical character in understanding phylogenetic relationships in Salicaceae. Further investigation is still needed on the tension wood of several other putatively close relatives of Salix and Populus, in particular Bennettiodendron, Macrohasseltia and Itoa .